The collection - Art Institute of Chicago (2006)
[Dt.:] Das Art Institute of Chicago ist ein 1866 gegründetes Kunstmuseum und eine Kunsthochschule in Chicago. Das Museum ist für seine umfangreiche Sammlung impressionistischer, post-impressionistischer und amerikanische Kunst bekannt. Die Werke können über eine Datenbank recherchiert werden. - [Engl.:] The Art Institute of Chicago is one of the premier fine art institutions in the United States. The Museum and the School are incorporated as equal partners. The Museum is known especially for its extensive collection of Impressionist, Post-Impressionist and American art. The works can be searched over a database.